Fuel Up to Play 60 program collaborative learning project guide - Schaefer, Elizabeth Porior (My University, 2013)
In summer of 2012, I realized the need for the Wisconsin Milk Marketing Board to create a curriculum for the Fuel Up to Play 60 program - a youth wellness program created by Dairy Marketing Inc. in partnership with the National Football League. The Fuel Up to Play 60 program enrolls over 2000 Wisconsin elementary and middle schools into the online program each year with only 19% of schools utilizing any one part of the program. I created a comprehensive curriculum for the Fuel Up to Play 60 program serve as a step-by-step guide for new and existing program advisors. This curriculum was designed to utilize the many resources of the Fuel Up to Play 60 website and break down the program into manageable, 45 minute lessons. The curriculum aligns to Wisconsin Grade 8 Common Core and Model Academic Standards in English Language, Agriculture Education, Health, Nutrition, Physical Education, Social Studies and Science Standards. The curriculum breaks the Fuel Up to Play 60 program into 8 lessons that can be taught as a collaborative unit of study or used as a guide for facilitating the program in a school setting. Each lesson includes electronic links to organize the many resources located at www.fueluptoplay60.com into the appropriate lesson, so that teachers may have quick access to the right information and resources at the appropriate time. The curriculum also includes supporting power points, assessments, and grading rubrics for utilization as part of a classroom curriculum. The final curriculum is available in digital form free of charge to instructors through the Wisconsin Dairy Council/ Wisconsin Milk Marketing Board.
Plan B Paper. 2013. Master of Science-Agricultural Education--University of Wisconsin-River Falls. Agricultural Education Department. iv + 34 leaves. Includes bibliographical references (leaf 14).
Keywords: Exercise; Nutrition--Study and teaching--Wisconsin; Physical fitness--Study and teaching--Wisconsin; Fuel Up to Play 60; Physical fitness; Nutrition; Exercise--Study and teaching--Wisconsin